WALTER STACE’S MORAL PROBLEM - Inst. Dr. Mustafa Razak Allawi (Journal of College of Education, 2024)
The philosophy of morals is not a new subject. Rather, it is one of the main branches of philosophy, and much more was written about this field. We see the English philosopher Walter Stace who tried to answer the question about The Concept of Morality, and whether it is relative or absolute. It is a famous question, but Walter Stace addressed it skillfully in preparing an answer through which he refutes common illusions, whether those which claim the relativity or absoluteness of morals. From the other side, we see the concept of Morals according to Stace that includes the arguments of the two main directions in Morality, and that is regarded as a history to this intellectual field. There is no doubt that Morals are full of problems and questions that require answers, the most important of which is the problems of Morals between the relative and absolute tendency, beside the relationship between happiness and pleasure, virtue and happiness, etc. therefore, Walter Stace was interested in studying many matters to Morals like freedom of will, the fundamentals of Morals, the goals of Morals, Morals and knowledge in the framework of relative and absolute tendency. He emphasized that the revolution of relativists against the doctrine of absolute Morality is part of general revolutionary trend to the era. , in particular, it is the product of decline belief in Orthodox religion in which the belief of Christian Monotheisms is a support to the absolute Morality.